Sources of the history of Oregon. - Young, Frederic G. (1897)
Contents.--pt. 1. Journal of Medorem Crawford. An account of his trip across the plains with the Oregon pioneers of 1842.--pt. 2. The Indian Council at Walla Walla, May and June, 1855, by Lawrence Kip.--pt. 3-6. The correspondence and journals of Captain Nathaniel J. Wyeth, 1831-6.